Terena agriculture and life-system. A speech and beyond - Maciel, Josemar de Campos; Surian, Alessio; Brahmllari, Estela; Tarasconi, Bibiane Ferreira; Antonio, Leosmar (Interações, 2019)
Abstract The paper comments on the relationship between the life system of an indigenous community and some issues related to development. It is structured around a core narrative provided by an indigenous leader. His speech is presented and annotated in order to make some of the claims more explicit. Comments are provided in order to contextualize and to elaborate on the oral speech’s intuitive dimension and ancestral wisdom. In the first place the paper seeks a pedagogical tension between reporting the speech as it was delivered to a group of students and key highlights and literature references that intend to expose this indigenous worldview concerning agriculture, education and development to a country such as Brazil that shows difficulties to listen to it. Resumo O artigo comenta a relação entre o sistema de vida de uma Comunidade Indígena Terena e alguns temas relacionados ao Desenvolvimento. Estrutura-se ao redor de uma narrativa de base, um discurso de um líder indígena. Apresentamos a sua preleção, com algumas anotações, para explicitar melhor o seu contexto e o seu alcance. Adicionamos comentários que contextualizam e elaboram reflexões a partir da dimensão mais intuitiva da fala, rica de sabedoria ancestral. O texto persegue uma tensão pedagógica entre a transmissão de uma fala apresentada a um grupo de estudantes, e algumas chaves de leitura e apontamentos que tentam expor o modo indígena de pensar e agir envolvendo a agricultura, educação e o desenvolvimento, em um país que anda tendo dificuldades para ouvir seu próprio povo.